PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING PADA MATERI PEMBELAJARAN EKOSISTEM UNTUK SISWA KELAS X SMA NEGERI 2 TABANAN - Ni Made Anindia Twi; Ni Putu Sri Ratna Dewi; I Made Oka Riawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the design, validity, and practicality of e-modules based on Problem Based Learning on ecosystem learning materials for class X MIPA students. This research is a Research and Development (R&D) study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Validity testing was carried out by media experts and material experts, while practicality testing was carried out by biology subject teachers and class X MIPA students. Data were analyzed descriptively, qualitatively, and quantitatively. The results show that (1) the design of this development research produced an e-module based on Problem Based Learning on ecosystem learning materials for class X MIPA students; (2) the validity of the e-module in terms of material obtained a Gregory Validity Coefficient value of 0.78, categorized as high, and in terms of media obtained a value of 0.66, also categorized as high; (3) the results of the teacher's practicality test showed an e-module practicality percentage of 98.2%, categorized as very practical, while the results of the students' practicality test showed a percentage of 87.57%, also categorized as very practical. Based on these results, the e-module based on Problem Based Learning is categorized as having high validity and being very practical for use as teaching material on ecosystem topics for class X MIPA.